The meaning of music – the reasons behind participation in one-day concerts and music festivals (Geography and Tourism, 2016)
The article is a result of field study conducted among the participants in the selected one-day concerts and festivals in Poland (such as Orange Warsaw, Open’er and Woodstock). The questionnaire was published online on the ankietaplus.pl website. The link to the questionnaire was made available on Facebook, selected social media related to concerts, and homepages of events chosen for research. The study aimed at creating and comparing the profiles of persons taking part in the above-mentioned music events. Moreover, the authors assessed tourist activity, as well as preferences and choices pertaining to music events. An attempt was made to indicate whether the visitors return for subsequent edi-tions of festivals or a given concert, and what are the reasons for (not) coming back. The research was performed in 2014 and involved as ample of 212 respondents.